In Silico Analytic of Antiacne Potential from Jamblang Flower’s Essential Oil Formulation - Hasibuan, Nurfadilah Azizah; Diningrat, Diky Setya; Sari, Ayu Nirmala (-, 2024)
This study aims to determine the components of compounds contained in Jamblang flower essential oil (Syzygium cumini L.) as antiacne and mechanism of antiacne. Jamblang flower essential oil is obtained through a distillation process. The distilled oil was then analysed using a Gas Chromatography Mass Spectrophotometer (GC-MS). Analysis results GC-MS evaluated using the program MASSLAB. Data obtained from the tool GC-MS then analysed using software PubChem NCBI database (https://pubchem.ncbi.nlm.nih.gov/) and PASS Online. The results of the GC-MS analysis showed that there were 47 bioactive compounds in Jamblang flower essential oil. Analysis results PubChem showed 13 compounds have activity as an antibacterial. Analysis results PASS Online demonstrated an antibacterial mechanism, protein synthesis inhibitor, membrane permeability inhibitor dan cell wall synthesis inhibitor, with the highest Pa value of 0.804 in the compound Benzyl benzoate $$Benzoic acid, phenylmethyl ester (CAS) and lowest Pa value in 1H-Benzimidazole,2-(methylthio)-(CAS)$$2-thiomethylbenzimidazole.